ZnSnO3 / NiO composite material, preparation method thereof and product containing ZnSnO3 / NiO composite material

By combining NiO nanosheets with ZnSnO3 hollow cubes, a p-n-type heterostructure composite material was constructed, which solved the problems of low response value and slow response speed of existing triethylamine gas sensors, and achieved high response, fast recovery and high selectivity gas sensing effects.

CN119660784APending Publication Date: 2025-03-21太原学院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411852633.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

At this stage, metal oxide-based triethylamine gas sensors have problems with low response value and slow response/recovery speed, which limits their application in actual fields.

Method used

By compositeing NiO nanosheets with ZnSnO3 hollow cubes, a p-n-type heterostructure composite material was constructed to prepare a triethylamine gas sensor.

Benefits of technology

The sensor is highly responsive and fast response/recovery speed, while improving selectivity, suitable for real-time monitoring of triethylamine gas leakage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660784A_ABST
    Figure CN119660784A_ABST
Patent Text Reader

Abstract

The invention discloses a ZnSnO3 / NiO composite material, a preparation method thereof and a product containing the ZnSnO3 / NiO composite material, and belongs to the technical field of gas sensors, the preparation method comprises the following steps: (1) mixing an ethanol solution containing a tin source and a sodium citrate aqueous solution containing a zinc source, and sequentially adding a first alkali liquor and a second alkali liquor into the mixed solution to obtain a precipitate 1, 2, 3, 4-tetramethyl-1, 3-pentanediol; then washing, drying and annealing are carried out, and a ZnSnO3 hollow cube is obtained; and (2) dissolving the ZnSnO3 hollow cubic block, nickel salt, urea and PVP in an ethanol aqueous solution, heating and stirring to obtain a precipitate 2, and then sequentially washing, drying and annealing to obtain the ZnSnO3 / NiO composite material which has a p-n type heterostructure, the triethylamine gas sensor prepared by taking the triethylamine as a sensitive material has the advantages of high response, fast response / recovery speed and high selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of gas sensors, and in particular relates to a ZnSnO3 / NiO composite material, a preparation method thereof, and a product containing the same. Background Art

[0002] Triethylamine is a volatile organic compound with an amine odor. It is widely used in many fields. For example, it can be used as a raw material, solvent and catalyst in industrial synthesis. It can also be used to prepare rubber vulcanization accelerators, enamel hardeners, liquid rocket propellants and acid collectors. In the pharmaceutical industry, triethylamine can be used to synthesize drugs such as vitamin B6, cefradine, berberine hydrochloride, Pioneer IV, and Viratin. However, the vapor or liquid of triethylamine can have a strong irritating effect on the mucous membranes and skin of the human body. When the human body inhales its vapor, it can cause damage to the central nervous system, mucous membrane tissues, liver and other body functions, and even death. Therefore, systematic research on the preparation technology and gas-sensing mechanism of triethylamine gas sensors is of great significance for real-time monitoring of triethylamine gas leakage and protecting human health.

[0003] So far, metal oxide semiconductor gas sensors have been widely used in the field of gas sensing due to their advantages such as low production cost, easy operation and stable performance. In order to cope with the increasingly complex gas monitoring needs, people realize the need to manufacture high-performance gas sensors, and the core issue is closely related to the design and preparation of new sensitive materials. However, although metal oxide-based triethylamine gas sensors have developed rapidly at this stage, such sensors still have problems such as low response value and slow response / recovery speed, which greatly limits their application in practical fields.

[0004] Therefore, there is an urgent need to provide a ZnSnO3 / NiO-based triethylamine gas sensor with high response and fast response / recovery speed and a preparation method thereof. Summary of the invention

[0005] In view of the above technical problems, the present invention proposes a ZnSnO3 / NiO composite material, a preparation method thereof and a product containing the same.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention:

[0008] A method for preparing a ZnSnO3 / NiO composite material comprises the following steps:

[0009] (1) mixing an ethanol solution containing a tin source and a sodium citrate aqueous solution containing a zinc source, and then sequentially adding a first alkali solution and a second alkali solution to the mixed solution to obtain a precipitate 1, and then washing, drying and annealing to obtain a ZnSnO3 hollow cubic block;

[0010] (2) The ZnSnO3 hollow cubes, nickel salt, urea and PVP are dissolved in an ethanol aqueous solution, heated and stirred to obtain a precipitate 2, and then washed, dried and annealed in sequence to obtain a ZnSnO3 / NiO composite material.

[0011] Beneficial effects: Through the above method, the present invention prepares a ZnSnO3 cubic block with a hollow structure, which is an n-type semiconductor material with the advantages of rich defect states and controllable chemical composition. NiO, as a typical p-type metal oxide semiconductor, has a wide band gap, large specific surface area, good structural stability, strong catalytic activity, high conductivity and oxygen adsorption capacity; the present invention composites NiO nanosheets and ZnSnO3 to construct a pn-type heterostructure composite material, which can increase the charge transfer between sensitive materials, thereby improving the gas-sensitive properties of pure ZnSnO3 materials.

[0012] Optionally, the tin source is a soluble tin salt, preferably SnCl4·5H2O;

[0013] The zinc source is a soluble zinc salt, preferably ZnCl2;

[0014] The molar ratio of tin atoms to zinc atoms in the tin source and the zinc source is 1:1.

[0015] Optionally, the first alkali solution is a 0.41M sodium hydroxide solution;

[0016] The second alkali solution is a 2M sodium hydroxide solution.

[0017] Optionally, the mass ratio of the ZnSnO3 hollow cube, urea and PVP in step (2) is 1:1:1;

[0018] The molar ratio of nickel atoms in the nickel salt to zinc atoms in the ZnSnO3 hollow cube is 1:(1-4), preferably 1:4, 1:2 and 1:1, and more preferably 1:2.

[0019] Optionally, the washing steps in step (1) and step (2) are both:

[0020] The precipitate 1 or precipitate 2 was washed with anhydrous ethanol and deionized water three times respectively and dried at 60-70°C.

[0021] Optionally, the annealing steps in step (1) and step (2) are both:

[0022] Anneal at 400°C-500°C for 2-5 hours.

[0023] The second technical solution of the present invention:

[0024] A ZnSnO3 / NiO composite material is prepared by the above preparation method.

[0025] Optionally, the ZnSnO3 / NiO composite material includes ZnSnO3 hollow cubic blocks and NiO nanosheets, wherein the NiO nanosheets are attached to the surface of the ZnSnO3 hollow cubic blocks; and the side length of the ZnSnO3 hollow cubic blocks is 2 μm.

[0026] The third technical solution of the present invention:

[0027] Application of the above ZnSnO3 / NiO composite material in the preparation of triethylamine gas sensor.

[0028] The fourth technical solution of the present invention:

[0029] A triethylamine gas sensor comprises a ceramic tube connected with two gold electrodes and a Ni-Cr alloy heating wire;

[0030] Wherein, the surface of the ceramic tube is coated with the above ZnSnO3 / NiO composite material.

[0031] The fifth technical solution of the present invention:

[0032] The preparation method of the triethylamine gas sensor comprises the following steps:

[0033] The ZnSnO3 / NiO composite material was mixed with anhydrous ethanol to obtain a slurry, which was then evenly coated on the surface of a ceramic tube connected to two gold electrodes;

[0034] The Ni-Cr alloy heating wire is inserted into the ceramic tube and welded to the base together with the test electrode lead wire, thereby preparing a triethylamine gas sensor.

[0035] Compared with the prior art, the present invention has the following advantages and technical effects:

[0036] The present invention compounds NiO nanosheets and ZnSnO3 hollow cubic blocks to construct a pn-type heterostructure composite material, which is used to prepare a triethylamine gas sensor, so that the sensor has the advantages of high response, fast response / recovery speed and high selectivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0038] Figure 1 a) is the XRD pattern of the ZnSn(OH)6 precursor (ZnSn(OH)6 hollow cube) sample in Example 1, b) is the XRD pattern of the ZnSnO3 and ZnSnO3 / NiO samples in Example 1;

[0039] Figure 2 a) and e) are FESEM images of the pure ZnSnO3 sample in Example 1, b) and f) are FESEM images of the ZnSnO3 / NiO-1 sample, c) and g) are FESEM images of the ZnSnO3 / NiO-2 sample, d) and h) are FESEM images of the ZnSnO3 / NiO-3 sample;

[0040] Figure 3 It is the element surface scanning analysis diagram of the ZnSnO3 / NiO-2 sample in Example 1;

[0041] Figure 4 a) and b) are TEM images of the ZnSnO3 / NiO-2 sample in Example 1, and c) is a HRTEM image of the ZnSnO3 / NiO-2 sample in Example 1; wherein, the inset of b) is a SAED image of the ZnSnO3 / NiO-2 sample in Example 1;

[0042] Figure 5 The XPS spectra of ZnSnO3 and ZnSnO3 / NiO-2 samples in Example 1; a) is the full spectrum, b) is Zn2p, c) is Sn 3d, d) is Ni 2p and f) is O1s; e) is the O1s spectrum of the ZnSnO3 sample;

[0043] Figure 6 Schematic diagram of the formation process of the ZnSnO3 / NiO composite material in Example 1;

[0044] Figure 7 a) is the response value of ZnSnO3 and ZnSnO3 / NiO based sensors to 100 ppm triethylamine at different temperatures in Example 1; b) is the change of the response value of ZnSnO3 and ZnSnO3 / NiO based sensors to 100 ppm of different VOCs at 220°C;

[0045] Figure 8a) is the response value of ZnSnO3 and ZnSnO3 / NiO based sensors to 5-200ppm triethylamine at 220°C in Example 1; b) is the relationship between the response value of ZnSnO3 and ZnSnO3 / NiO based sensors and the concentration of triethylamine; c) is the response / recovery curve of ZnSnO3 / NiO-1, d) is ZnSnO3 / NiO-2 and e) is the response / recovery curve of ZnSnO3 / NiO-3 based sensors to 100ppm triethylamine gas at 220°C; f) is the repeatability of ZnSnO3 / NiO-2 based sensors;

[0046] Fig. 9 1 and 2 are the energy band diagram a) and the sensitive mechanism schematic diagram b) of the ZnSnO3 / NiO composite material in an embodiment of the present invention. DETAILED DESCRIPTION

[0047] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0048] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0049] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0050] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0051] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0052] The raw materials used in the present invention are all purchased from the market.

[0053] The technical solution of the present invention is further illustrated by the following embodiments.

[0054] Example 1

[0055] A method for preparing a triethylamine gas sensor based on a ZnSnO3 / NiO composite material comprises the following steps:

[0056] 1. Synthesis of ZnSnO3 / NiO composites

[0057] (1) Synthesis of ZnSnO3 hollow cubes:

[0058] 10 mL of SnCl4·5H2O ethanol solution (0.2 M) was dissolved in 20 mL of an aqueous solution containing 0.1 M ZnCl2 and 0.1 M sodium citrate; after 15 minutes, 50 mL of NaOH solution (0.41 M) was slowly dripped into the above solution and stirred for 30 minutes to obtain ZnSn(OH)6 solid cubes; then 30 mL of NaOH solution (2 M) was added thereto to obtain ZnSn(OH)6 hollow cubes; the generated white precipitate was then washed three times with anhydrous ethanol and deionized water respectively and dried at 60°C; finally, the dried sample was annealed at 450°C for 2 hours to obtain ZnSnO3 hollow cubes.

[0059] (2) Synthesis of ZnSnO3 / NiO composite materials:

[0060] 0.04g of the generated ZnSnO3 hollow cubes, different amounts of Ni(NO3)2·6H2O, 0.04g of urea and 0.04g of PVP were added to a mixed solution of 70mL of ethanol and 10mL of water and stirred; after 10 minutes, the solution was heated to 70℃ and stirred for 10 hours to generate a precipitate; then the precipitate was washed with anhydrous ethanol and deionized water for 3 times each and dried at 60℃; finally, the dried powder was annealed at 450℃ for 2 hours at a heating rate of 1℃ / min. Among them, the addition amount of Ni(NO3)2·6H2O was added according to the following ratios, and the molar ratios of Ni and Zn were 1:4, 1:2 and 1:1 respectively. The prepared ZnSnO3 / NiO composite materials were named ZnSnO3 / NiO-1, ZnSnO3 / NiO-2 and ZnSnO3 / NiO-3 respectively.

[0061] 2. Preparation of gas sensor (triethylamine gas sensor) based on ZnSnO3 / NiO composite material

[0062] The synthesized ZnSnO3 / NiO composite material was mixed with anhydrous ethanol, and then a paste slurry was obtained by stirring and evenly applied to the surface of a ceramic tube connected to two gold electrodes with a brush;

[0063] Then the Ni-Cr alloy heating wire is inserted into the ceramic tube and welded to the base together with the test electrode lead, thereby forming a indirectly heated gas sensor, wherein the operating temperature of the gas sensor can be controlled by adjusting the current flowing through the heating wire.

[0064] Effect verification:

[0065] 1. Sample Characterization

[0066] The crystal structure of the above samples was analyzed by XRD: Figure 1 Figure a) is the XRD spectrum of the ZnSn(OH)6 precursor. It can be seen from the figure that all diffraction peaks correspond to the standard peaks of cubic phase ZnSn(OH)6 (JCPDS No.74-1825), and there are no additional peaks, indicating that the generated sample is pure ZnSn(OH)6. The XRD spectra of ZnSnO3 material and ZnSnO3 / NiO composite material are shown in Figure 2. Figure 1 As shown in (b). It can be seen from the figure that the diffraction peak of the sample corresponds to the diffraction peak of the standard ZnSnO3 phase. In addition, no sharp and high-intensity diffraction peaks are observed in the figure, indicating that the crystallinity of the sample is relatively weak.

[0067] The morphology and structure of the samples were observed by FESEM: Figure 2 The FESEM images of ZnSnO3 samples prepared by combining pure ZnSnO3 with different amounts of NiO are shown in Figure 1. As can be seen from the figure, these samples are composed of a large number of uniform and well-shaped hollow cubic blocks. In addition, as the NiO content increases, the number of nanosheets attached to the surface of the ZnSnO3 cubic blocks also increases gradually.

[0068] Furthermore, the element surface scanning analysis of ZnSnO3 / NiO-2 samples was carried out, such as Figure 3 As shown in the figure, it can be seen that Zn, Sn, O and Ni elements are evenly distributed in the sample.

[0069] The microstructure of the samples was further analyzed by TEM. Figure 4 Figure a) is a TEM image of a single ZnSnO3 / NiO-2 sample. From the figure, it can be seen that there is a clear contrast between the inner area of ​​the cube and the outer shell, proving that the synthesized sample is a hollow cube, and its side length is about 2μm, which is consistent with the FESEM characterization results. The enlarged TEM image of the ZnSnO3 / NiO-2 sample is shown in Figure 2. Figure 4As shown in (b), it can be seen from the figure that many NiO nanosheets are attached to the surface of the ZnSnO3 cube, indicating that a pn-type heterostructure composed of ZnSnO3 and NiO has been formed. Figure 4 The inset of (b) is the SAED image of the ZnSnO3 / NiO-2 sample. The diffraction rings can be clearly seen from the figure, indicating that the ZnSnO3 / NiO-2 sample is a polycrystalline structure. The HRTEM image of the ZnSnO3 / NiO-2 sample is shown in Figure 1. Figure 4 The lattice spacing in the flake region was measured to be 0.211 nm, corresponding to the (200) crystal plane of NiO, indicating that NiO has been successfully attached to the surface of the ZnSnO3 cube.

[0070] The elemental composition and valence state of pure ZnSnO3 and ZnSnO3 / NiO-2 samples were analyzed by XPS. Figure 5 shown. Figure 5 Figure a) is the full spectrum of the ZnSnO3 / NiO-2 sample. It can be seen from the figure that the sample is mainly composed of Zn, Sn and O elements, and the peak of Ni element also appears in the spectrum. Figure 5 b) is the Zn 2p spectrum of the ZnSnO3 / NiO-2 sample. The peaks at 1022.2eV and 1045.4eV correspond to Zn 2p 3 / 2 and Zn 2p 1 / 2 , indicating that the valence state of Zn ions in the sample is divalent. Figure 5 c) is the Sn 3d spectrum of ZnSnO3 / NiO-2 sample. The peaks at 486.7eV and 495.3eV correspond to Sn3d 5 / 2 and Sn 3d 3 / 2 , indicating that the valence state of Sn ions in the sample is positive tetravalent. Figure 5 (d) is the Ni 2p spectrum of the ZnSnO3 / NiO-2 sample. The peaks at 854.9 eV and 861.1 eV correspond to Ni 2p 3 / 2 , while the peaks at 872.9 eV and 879.4 eV correspond to Ni 2p 1 / 2 , indicating the presence of NiO in the sample. Figure 5 e) and Figure 5f) are the O1s spectra of pure ZnSnO3 and ZnSnO3 / NiO-2 samples. After fitting, the two asymmetric O1s peaks can be divided into three peaks. The peaks at around 530.1eV, 530.9eV and 531.9eV correspond to lattice oxygen, oxygen defects and surface adsorbed oxygen, respectively. In addition, in the pure ZnSnO3 sample, the proportions of lattice oxygen, oxygen defects and surface adsorbed oxygen are 52.3%, 18.3% and 29.5%, respectively, while in the ZnSnO3 / NiO-2 sample, the proportions of lattice oxygen, oxygen defects and surface adsorbed oxygen are 37.7%, 26.5% and 35.8%, respectively. It can be clearly seen that when NiO nanosheets are attached to the surface of ZnSnO3, the proportions of oxygen defects and surface adsorbed oxygen in the sample are significantly improved, which will also significantly improve the gas-sensitive properties of the sensitive material.

[0071] 2. Growth Mechanism Analysis

[0072] Figure 6 Schematic diagram of the formation process of ZnSnO3 / NiO composite materials. (i) Growth process of ZnSn(OH)6 hollow cubes: Zn 2+ Sn 4+ OH - The coprecipitation reaction rate between ZnSn(OH)6 and citrate ion is very fast, and due to the cubic crystal structure of ZnSn(OH)6 itself, solid cubic blocks of ZnSn(OH)6 are quickly generated. - Afterwards, these generated solid cubes will be connected with OH - interact to form a soluble [Sn(OH)6] 2- and [Zn(OH)4] 2- . And because the outer structure of the ZnSn(OH)6 cube has better stability than the inner structure, the solid ZnSn(OH)6 cube is eventually transformed into a hollow cube. (ii) Formation process of ZnSnO3 / NiO composite material: After the ZnSn(OH)6 sample is treated at high temperature, ZnSn(OH)6 will remove water from the structure and completely transform into ZnSnO3. Next, different amounts of Ni(NO3)2·6H2O are added to the ZnSnO3 ethanol aqueous solution (containing urea and PVP). 2+ will be adsorbed onto the surface of the ZnSnO3 sample. At the same time, the urea in the solution will hydrolyze to release NH3 and CO2, making the solution alkaline. 2+ Will be with OH -The reaction generates Ni(OH)2. When the solution is stirred at 70°C for 10 hours, Ni(OH)2 will be evenly attached to the surface of the ZnSnO3 cube. Finally, the sample was annealed to successfully obtain the ZnSnO3 / NiO composite material. The relevant chemical reaction equation is as follows:

[0073] ZnSn(OH)6→ZnSnO3+3H2O················(1)

[0074] CO(NH2)2+H2O→CO2+2NH3······················(2)

[0075]

[0076] Ni 2+ +2OH - →Ni(OH)2·······················(4)

[0077] Ni(OH)2→NiO+H2O·······················(5)

[0078] 3. Gas Sensing Performance Analysis

[0079] 1. Generally speaking, the performance of the sensor is closely related to its operating temperature. Therefore, the response values ​​of pure ZnSnO3 and ZnSnO3 / NiO-based sensors to 100ppm triethylamine were first tested at 180℃-260℃. Figure 7 As shown in a). It can be seen that the response values ​​of the four sensors all show a trend of increasing first and then decreasing, and show the maximum response value at 220°C, so their optimal operating temperatures are all 220°C. This is because sufficient energy is generated at this temperature, so that the surface of the sensitive material has more chemically adsorbed oxygen, which promotes the chemical reaction between it and the test gas molecules, thereby improving the response value of the sensor. However, as the operating temperature increases, the previously adsorbed gas molecules will escape from the surface of the material before the chemical reaction, resulting in a decrease in the sensor response value. In addition, the response value of the ZnSnO3 / NiO-based sensor is much greater than that of the pure ZnSnO3-based sensor, indicating that the composite of NiO can greatly improve the performance of the sensor, and the response value of the ZnSnO3 / NiO-2-based sensor is the largest.

[0080] 2. Gas selectivity is also an important indicator for evaluating the performance of sensors. Figure 7(b) shows the response value changes of the four sensors at 220°C to 100ppm of different VOCs including ethanol, acetone, methanol, benzene, formaldehyde and triethylamine gas. As can be seen from the figure, all four sensors show the highest response to triethylamine gas. However, the response values ​​of the pure ZnSnO3-based sensor to triethylamine gas and other test gases are almost the same, indicating that it has poor selectivity. However, the response values ​​of the three ZnSnO3 / NiO-based sensors to triethylamine gas are much greater than those to other test gases, so they have good selectivity. It is proved that the composite of NiO and ZnSnO3 not only improves the response value of the sensor but also improves its selectivity.

[0081] Figure 8 Figure a) shows the response curve of pure ZnSnO3 and ZnSnO3 / NiO based sensors to 5-200ppm triethylamine at 220°C. As can be seen from the figure, as the concentration of triethylamine increases, the response values ​​of the four sensors also increase accordingly. Specifically, the response values ​​of the pure ZnSnO3 based sensor to 10, 20, 50, 100 and 200ppm triethylamine gas are 1.16, 3.45, 7.2, 11.5 and 16.1 respectively. The response values ​​of the ZnSnO3 / NiO-1 based sensor to 5, 10, 20, 50, 100 and 200ppm triethylamine gas are 1.15, 1.8, 3.9, 10.9, 21.4 and 40.9 respectively. The response values ​​of ZnSnO3 / NiO-2 based sensor to 5, 10, 20, 50, 100 and 200 ppm triethylamine gas are 3.1, 4.2, 10.7, 28.8, 70.6 and 104.6 respectively, while the response values ​​of ZnSnO3 / NiO-3 based sensor to 5, 10, 20, 50, 100 and 200 ppm triethylamine gas are 2.1, 3.2, 6.9, 15.3, 28.7 and 52.5 respectively. Figure 8 (b) is the relationship curve between the response value of pure ZnSnO3 and ZnSnO3 / NiO-based sensors to triethylamine at 220°C and the gas concentration. It can be seen that the response values ​​of all sensors increase with the increase of triethylamine gas concentration. In addition, the response values ​​of the three ZnSnO3 / NiO-based sensors to triethylamine gas are higher than those of the pure ZnSnO3-based sensor, and the ZnSnO3 / NiO-2-based sensor shows the highest response to triethylamine gas, indicating that the composite of NiO greatly improves the response value of the sensor, and the optimal composite amount is when the molar ratio of Ni to Zn is 1:2.

[0082] The response / recovery speed of the sensor is also an important parameter for evaluating the performance of the gas sensor. Figure 8Figures c)-e) are the response / recovery curves of three ZnSnO3 / NiO-based sensors to 100 ppm triethylamine at 220°C. It can be seen from the figure that the response / recovery times of ZnSnO3 / NiO-1, ZnSnO3 / NiO-2 and ZnSnO3 / NiO-3 based sensors are 1s / 31s, 1s / 18s and 1s / 23s respectively. Figure 8 f) indicates the repeatability of the ZnSnO3 / NiO-2 based sensor. After the ZnSnO3 / NiO-2 based sensor was placed in 100ppm triethylamine gas at 220℃ for four consecutive cycles of response / recovery test, the response value and response / recovery speed of the sensor did not change significantly, indicating that the sensor has good repeatability.

[0083] 4. Gas Sensing Mechanism

[0084] From the test results, we can see that the ZnSnO3 / NiO-based sensor exhibits good gas-sensing performance to triethylamine, which can be attributed to the following reasons (such as Fig. 9 shown):

[0085] First, since NiO is a typical p-type semiconductor material, when NiO nanosheets are attached to the surface of the ZnSnO3 hollow cube, electrons will be transferred from the ZnSnO3 side to the NiO side, while holes will move in the opposite direction until the Fermi level of the system reaches equilibrium, resulting in the formation of a contact barrier at the interface between ZnSnO3 and NiO, while also generating a built-in electric field. Therefore, an electron depletion layer will be generated at the interface close to the ZnSnO3 material side, and a hole depletion layer will be formed at the interface close to the NiO material side, resulting in an increase in the resistance of the ZnSnO3 / NiO-based sensor in the air. When the ZnSnO3 / NiO-based sensor is exposed to triethylamine gas, electrons will be released, causing the depletion layer thickness to become narrower, so the barrier height will also decrease accordingly. Moreover, the relationship between the resistance (R) and barrier height (Φ) of the heterostructure can be expressed by the following equation:

[0086] R∝Be (q Φ / KT)····················(6)

[0087] In the above formula, B is a temperature-related constant, q is the electron charge, K is the Boltzmann constant, and T is the absolute temperature. From the above formula, it can be analyzed that a slight change in the barrier height can significantly change the resistance of the sensor. Therefore, the response value of the sensor can be greatly improved by constructing a ZnSnO3 / NiO composite material. Moreover, NiO itself has strong catalytic activity, which can promote the adsorption of oxygen molecules on the surface of the material, thereby generating more chemically adsorbed oxygen and enhancing its chemical reaction with triethylamine molecules. In addition, it can be concluded from XPS analysis that the content of oxygen defects in ZnSnO3 / NiO-2 materials is higher than that of pure ZnSnO3 materials, so more chemically adsorbed oxygen will also be generated on the surface of ZnSnO3 / NiO-2 materials, resulting in improved sensor performance. However, when too many NiO nanosheets are attached to the surface of ZnSnO3, the response value of the sensor will decrease, which may be due to the excessive NiO covering the active sites on the surface of the material.

[0088] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A ZnSnO3 / NiO composite material, characterized in that: The ZnSnO3 / NiO composite material comprises ZnSnO3 hollow cubic blocks and NiO nanosheets, wherein the NiO nanosheets are attached to the surface of the ZnSnO3 hollow cubic blocks.

2. A method for preparing the ZnSnO3 / NiO composite material as claimed in claim 1, characterized in that: The following steps are involved: (1) mixing an ethanol solution containing a tin source and a sodium citrate aqueous solution containing a zinc source, and then sequentially adding a first alkali solution and a second alkali solution to the mixed solution to obtain a precipitate 1, and then washing, drying and annealing to obtain a ZnSnO3 hollow cubic block; (2) The ZnSnO3 hollow cubes, nickel salt, urea and PVP are dissolved in an ethanol aqueous solution, heated and stirred to obtain a precipitate 2, and then washed, dried and annealed in sequence to obtain a ZnSnO3 / NiO composite material.

3. The method for preparing a ZnSnO3 / NiO composite material according to claim 2, characterized in that: The molar ratio of nickel atoms in the nickel salt to zinc atoms in the ZnSnO3 hollow cube is 1:(1-4).

4. The method for preparing a ZnSnO3 / NiO composite material according to claim 3, characterized in that: The molar ratio of nickel atoms in the nickel salt to zinc atoms in the ZnSnO3 hollow cube is 1:

2.

5. The method for preparing a ZnSnO3 / NiO composite material according to claim 2, characterized in that: In step (1), the molar ratio of tin atoms to zinc atoms in the tin source and the zinc source is 1:1; The mass ratio of the ZnSnO3 hollow cube, urea and PVP in step (2) is 1:1:

1.

6. The method for preparing a ZnSnO3 / NiO composite material according to claim 2, characterized in that: The washing steps in step (1) and step (2) are both: The precipitate 1 or precipitate 2 was washed with anhydrous ethanol and deionized water three times respectively and dried at 60-70°C.

7. The method for preparing a ZnSnO3 / NiO composite material according to claim 2, characterized in that: The annealing steps in step (1) and step (2) are both: Anneal at 400°C-500°C for 2-5 hours.

8. Use of the ZnSnO3 / NiO composite material as claimed in claim 1 in preparing a triethylamine gas sensor.

9. A triethylamine gas sensor, characterized in that: It includes a ceramic tube connected to two gold electrodes and a Ni-Cr alloy heating wire; Wherein, the surface of the ceramic tube is coated with the ZnSnO3 / NiO composite material as claimed in claim 1.

10. A method for preparing a triethylamine gas sensor, characterized in that: The following steps are involved: The ZnSnO3 / NiO composite material according to claim 1 is mixed with anhydrous ethanol to obtain a slurry, and then uniformly coated on the surface of a ceramic tube connected to two gold electrodes; The Ni-Cr alloy heating wire is inserted into the ceramic tube and welded to the base together with the test electrode lead, thereby preparing the triethylamine gas sensor described in claim 9.